Fuzzy modeling of the effect of irrigation depths on beet cultivars - Filho, Luís R. A. Gabriel [UNESP]; da Silva, Alexsandro O.; Cremasco, Camila Pires [UNESP]; Putti, Fernando Ferrari [UNESP] (FapUNIFESP (SciELO), 2022)
The objective of this study was to develop a Fuzzy Rule-Based System (FRBS) for the mathematically modeling of the irrigation level effect on beet cultivars (Beta vulgaris L.). From an agronomic experiment carried out in a protected environment (greenhouse), it was defined as input variables, for each cultivar, the irrigation levels (depths of 25, 40, 55, 70, 85, and 100% of ETc), in which ETc is the crop evapotranspiration [mm d-1], while the output variables were productivity, root diameter, and plant height. Was adopted the inference method of Mamdani and centroid method for fuzzification. The fuzzy models performed better than polynomial regression models, when compared with the coefficients of determination (R²), mean absolute error (MAE) and root mean square error (RMSE). In addition, the excellent performance of the model is highlighted due to the curve containing all the points of the treatments means. As agronomic results, concluded that the Early Wonder cultivar has higher yields when submitted to water deficit.
Keywords: Artificial intelligence; Beet; Fuzzy logic; Production; Water deficit